Analysis of Stress and Strain in Sandwich Structures Using an Equivalent Finite Element Model - Lien Tien Dao; Pham Tuong Minh Duong; Viet Dung Luong (International Journal of Engineering and Technology Innovation, 2025)
The study aims to build an equivalent 2D model as an alternative to the 3D model of sandwich panel structures. This model enables for reducing model building time and calculation time in the design calculation of this sandwich structure. The research object in this study is corrugated core cardboard. First, the isotropic plasticity equivalent (IPE) model for the paper material is implemented in the Abaqus software, using the VUMAT user subroutine. Subsequently, the homogenization method is proposed as an equivalent elastic-plastic finite element model. This model is implemented in Abaqus using the UGENS subroutine. Finally, numerical simulations of different load cases between the 3D model and the equivalent 2D model are performed to confirm the accuracy of the proposed model. The comparison results indicate that the equivalent model ensures exceptional accuracy compared to the 3D model but significantly reduces model building time and CPU time.